2017
DOI: 10.1002/hep.28926
|View full text |Cite
|
Sign up to set email alerts
|

Optimal timing of hepatitis C treatment for patients on the liver transplant waiting list

Abstract: The availability of oral direct-acting antiviral (DAAs) has altered the hepatitis C virus (HCV) treatment paradigm for both pre- and post-liver transplant (LT) patients. There is a perceived trade-off between pre- versus post-LT treatment of HCV—treatment may improve liver function but potentially decrease the likelihood of a necessary LT. Our objective was to identify LT-eligible patients with decompensated cirrhosis who would benefit (and not benefit) from pre-LT treatment based on their MELD scores. We simu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
86
0
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(90 citation statements)
references
References 42 publications
1
86
0
3
Order By: Relevance
“…The potential adverse consequences of this may be more marked in the UK as waiting time for liver transplantation is longer than other countries. The MELD cut off has been reported as a point beyond which the probability of harm from DAA therapy is greater than the probability of benefit …”
Section: Discussionmentioning
confidence: 99%
“…The potential adverse consequences of this may be more marked in the UK as waiting time for liver transplantation is longer than other countries. The MELD cut off has been reported as a point beyond which the probability of harm from DAA therapy is greater than the probability of benefit …”
Section: Discussionmentioning
confidence: 99%
“…Other studies have investigated the optimal timing of DAA treatment for patients listed for transplant, using a decision analytical model . The first was the study by Njei et al that considered only patients with decompensated cirrhosis without HCC.…”
Section: Discussionmentioning
confidence: 99%
“…This study also confirms that treatment prior to LT is the most cost‐effective for patients with a MELD>10. A third study from Chatwal et al evaluated the trade‐off between treating HCV patients with decompensated cirrhosis before or after LT considering only the change in life expectancy without including the cost and QALYs associated with the treatment strategies. Once again, the PRE‐LT treatment emerged as more effective for patients with a MELD score lower than 23.…”
Section: Discussionmentioning
confidence: 99%
“…When suffering from HCV and receiving DAAs, MELD score decreases, leading to a longer wait-list time with potential negative impact on mortality. In a recent study by Chhatwal et al, MELD scores between 23 and 27 were identified as optimal time point (in the US setting) to better defer DAA treatment to the early post‐OLT period. Currently, there exists no specific medical treatment for NAFLD, thus lifestyle interventions and physical activity should be recommended. Mild strength training seems beneficial because this might counteract sarcopenia, which is associated with significantly worse outcomes both on the waiting list and after OLT …”
Section: Special Considerations For Patients On the Orthotopic Lt Waimentioning
confidence: 99%